Analyzing Factors Influencing Consumer Purchase Behavior of Generation Z toward Second-Hand Apparel in Indonesia (Journal of Business and Management, 2022)
Second hand apparel has become a trend that gradually increases in the development of the fashion industry. Generation Z as target customers have intrinsic and extrinsic motivation that drive their purchase behavior for a product. Understanding the motivations behind second-hand clothing consumption can assist in building marketing expertise in the fashion business, since generation Z will have tremendous buying power in the next few years. This study was conducted to achieve competitiveness from this big opportunity and comprehend the most influential factors (attitudes, subjective norms, perceived behavioral control, and physical vanity aspect) that shape and encourage purchase behavior, by combining the theory of planned behavior and physical of vanity. The author employs Partial Least Square Structural Equation Modeling (PLS-SEM) using Smart-PLS to evaluate data from 327 online survey respondents. The subjective norm found as the most significant factor of purchase intention, followed by attitude and perceived behavioral control. Moreover, perceived physical vanity influences purchase behavior. Younger consumers are more influenced by their external motive to buy secondhand clothing. This data may help marketers enhance their marketing strategies by highlighting social values, such as social acceptability, which influences generation Z's purchase behavior for second hand clothing.